Acid-Base and Electrolytes Profile in Critically Ill Pediatric Patients Admitted to Pediatric Intensive Care Unit (PICU) (Majalah Kedokteran Bandung, 2025)
Critically ill pediatric patients are known to experience more frequent episodes of acid-base and electrolyte imbalances when compared to adults, which can significantly impact morbidity and mortality with higher mortality rates and longer hospital stays. Data on the profile of acid-base and electrolyte imbalances in critically ill pediatric patients is very limited in Indonesia. This study was conducted to describe the electrolytes and acid-base profile of critically ill pediatric patients admitted to the Pediatric Intensive Care Unit (PICU). This was a cross-sectional study using secondary data from medical records of critically ill pediatric patients aged 1 month to 18 years admitted to the PICU of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from January 1 to December 31, 2021. Results indicated that 131 (50.8%) of 258 patients experienced electrolytes and acid-base imbalances. The majority of patients were boys (53.0%) and infants (32.8%). The most common primary diagnosis was respiratory (28.2%), central nervous system (19.8%), and gastrointestinal disorders (15.3%). A total of 366 electrolyte imbalance events and 111 acid-base imbalance events were recorded. The most common electrolyte imbalance events were hyponatremia (75.6%), hypocalcemia (48.9%), and hypokalemia (42.7%), respectively, while the most frequent acid-base imbalance events were respiratory alkalosis (33.6%) and metabolic acidosis (21.4%). Electrolyte and acid-base imbalances are common among critically ill pediatric patients in PICU. Thus, early evaluation and recognition of acid-base and electrolyte imbalances are crucial in order to prevent poor outcomes in these patients.
Keywords: acid-base; critically ill; electrolyte; pediatric intensive care units